2016
DOI: 10.1186/s12891-016-0895-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor enhances lipopolysaccharide-induced fibroblast proliferation by inducing toll-like receptor 4

Abstract: BackgroundFibroblast proliferation is a common manifestation of chronic inflammatory diseases, including rheumatoid arthritis (RA), Crohn’s disease and ulcerative colitis, etc. To alleviate patient suffering, the mechanism underlying fibroblast proliferation should be elucidated.MethodsCCK-8 assay was used to assess the stimulatory effect of LPS and macrophage migration inhibitory factor (MIF) on fibroblast proliferation. Then, TLR4 expression on fibroblast cell membrane was carried out by confocal scanning mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…As reported in previous studies, LPS stimulation is able to maintain high levels of cell viability (30,31). The addition of compound 1 was demonstrated to be able to preserve this beneficial effect, allowing the maintenance of a high rate of cell viability throughout the treatment.…”
Section: Discussionsupporting
confidence: 68%
“…As reported in previous studies, LPS stimulation is able to maintain high levels of cell viability (30,31). The addition of compound 1 was demonstrated to be able to preserve this beneficial effect, allowing the maintenance of a high rate of cell viability throughout the treatment.…”
Section: Discussionsupporting
confidence: 68%
“…PDGFBB is a well-known growth factor that stimulates the proliferation of ASMCs (Ito et al, 2009;Hirota et al, 2011;Yang et al, 2016). Interestingly, we observed that PDGFBB upregulated the expression of MIF, which has been reported to promote cell proliferation in several studies Guo et al, 2015;Xie and Xi, 2016). In the present study, we found that overexpression of MIF markedly promoted cell cycle progression and cell proliferation in ASMCs.…”
Section: Discussionsupporting
confidence: 63%
“…In our system, a modest effect was observed particularly in infected cells at 25 ng/ml MIF with no evidence of CD74 participation. A more recent report indicated that exogenously added MIF could modulate TLR4 in murine fibroblasts but only at 375 ng/ml MIF (15-fold higher concentration than in our system) ( 62 ). Regardless MIF stimuli, it is also worth pointing that TLR4 expression was lower in bystander cells, compared to the uninfected condition.…”
Section: Discussionmentioning
confidence: 59%